TBCCD1 is a key regulator of centrosomal microtubule anchor and basal body positioning/attachment - Carmona, Bruno (2019)
Successful cilia assembly requires correct positioning and anchoring of the centrosome's mother centriole/basal body (BB) to the cell membrane. A clear picture of the different signals and players involved in centrosome positioning/anchoring is still not available. Published work from our group identified a new TBCC domain-containing human protein (TBCCD1). Depletion of TBCCD1 in human RPE-1 cells severely affects the relative position of the centrosome to the nucleus and the efficiency of cells to assemble primary cilia. Aim of the study: To dissect the mechanisms involving TBCCD1 in human RPE-1 positioning and anchoring during ciliogenesis.